Analisis Biaya dan Waktu Percepatan Proyek Pembangunan Rusun At-Tanwir Cianjur dengan Penambahan Jam Kerja Menggunakan Metode TCTO - Nurhikmah, Salmah; Dewita, Hikma; Sembiring, Kristina (Universitas Ibn Khaldun, 2025)
The At-Tanwir Foundation’s Flats Construction Project at Cianjur Regency, West Java; aims to provide housing for students and promote education. Therefore, expediting the construction process for immediate utilization is essential to meet the housing needs. One alternative for expediting the project is to increase working hours using the time-cost trade-off method. The purpose of acceleration is to anticipate delays in the project and shorten the project implementation time. This study uses data such as Project RAB, Plan S Curve, a List of Unit Prices of Materials, Tools, and Labor, and an Analysis of Unit Prices of Work. Microsoft Project 2019 software assists in data processing to identify critical paths. After accelerating work on critical activities, the analysis showed that by adding 3 hours of overtime, the project duration can be reduced to 100 working days, which is 15% faster than the normal duration of 119 working days. The optimal cost for this duration is IDR 808,750,195.52, which is 0,69% lower than the normal cost of IDR 803,164,902.33, with a cost difference of IDR 5,585,293.19.